Low Cost and Centimeter-Level Global Positioning System Accuracy Using Real-Time Kinematic Library and Real-Time Kinematic GPSA - Gianey, Hemant K.; Ali, Mumtaz; Vijayakumar, Varadarajan; Sharma, Ashutosh; Kumar, Rajiv (Recent Advances in Computer Science and Communications, 2021)
Introduction: Accuracy and total design and implementation cost of the GPS framework determine the viability of GPS based projects. As the greater part of the advanced framework including telemetry, IoT, Cloud, and AUTOSAR frameworks use GPS to get exact outcomes, finding a software-controlled error correction becomes important. The execution of open source library such as RTKLIB will help in controlling and revising GPS blunders. Methods: The project utilizes the RTKLIB along with two stations for better accuracy. The RTKGPS framework works under Linux environment, which is embedded in the Beagleboard. The communication between the GPS system is set up utilizing both serial communication protocol and TCP/IP suite. Results: To get high precision inside the network, two GPS modules are utilized. One of them will be mounted on the rover and another GPS is the base station of the setup. Both the GPS will have a double radio wire setup to increase the reception level to reduce the noise and obtain centimeterlevel precision. For long-range communication, rover utilizes Wi-Fi with TCP/IP stack protocol. In this research paper, setup is intended to accomplish the centimeter level precision through libraries in a Linux environment. Conclusion: The design will be set up and tried on a college campus under various conditions with different error parameters to acquire a low cost and centimeter level GPS accuracy.
Keywords: RTKLIB